PENGARUH KNOWLEDGE SHARING TERHADAP KOMPETENSI KARYAWAN MELALUI BUDAYA ORGANISASI SEBAGAI MEDIATOR: Study At PT. Telkom Indonesia Regional III Jawa Barat - Panggabean, Elizabeth Romaito; Silvianita, Anita (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
This study was conducted to determine the effect of knowledge sharing on employee competencies with organizational culture as a mediator. The purpose of this study was to analyze and examine the direct and indirect effects between the variables in this study include knowledge sharing, employee competencies, and mediated with the organizational culture at PT. Telkom Indonesia Regional III Jawa Barat. The method used in this study is a quantitative method, with a type of descriptive-causal analysis. Sampling with non-probability sampling with a type of sampling jenuh with a sample of 100 respondents taken from employees of PT. Telkom Indonesia Regional III Jawa Barat. Data analysis techniques used are descriptive analysis techniques and Partial Least Square analysis – Structural Equation Model (PLS-SEM) with SmartPLS analysis tools. The results of this analysis show the organizational culture as a mediator in partial mediation resulting in changes or impairment of knowledge sharing variables to the employee's competence. Organizational culture makes knowledge sharing to influence competencies indirectly become insignificant, it can be concluded that the culture of the organization is still not able to give the influence of good mediator. Keywords: knowledge Sharing, Competencies, Organizational culture